Bio-butanol production from rice straw – Recent trends, possibilities, and challenges. (September 2019) - Vivek, Narisetty; Nair, Lakshmi M.; Mohan, Binoop; Nair, Salini Chandrasekharan; Sindhu, Raveendran; Pandey, Ashok; Shurpali, Narasinha; Binod, Parameswaran
Abstract: Increase in concerns over greenhouse gas emissions and depletion of fossil fuels has led to the search for alternative strategies of energy. Rice straw mainly composed of cellulose, hemicelluloses, and lignin, is one of the surpluses available lignocellulosic biomass that can serve as a potential feedstock for the production of bio-butanol. One of the main challenges in the conversion of rice straw to bio-butanol is the development of an economically viable and eco-friendly pretreatment strategy for better hemicellulose and lignin removal as well as the development of hyper-productive and solvent-tolerant microbial strains for effective fermentation. This review focuses on the recent trends, challenges, and possibilities in the production of butanol utilizing rice straw. Graphical abstract: Unlabelled Image Highlights: Overview of bio-butanol production from rice straw Recent developments in bio-butanol production Challenges in bio-butanol production